A combined behavioural and electrophysiological examination of the faulty foraging theory of probability matching - Ellerby, Zack W. (2018)
Given a repeated choice between two or more options with fixed, independent and identically distributed reward probabilities, overall pay-offs can be maximized by the exclusive selection of the option with the greatest likelihood of reward. The tendency to match response proportions to reward contingencies is suboptimal. Nevertheless, this behaviour is well documented. This thesis had two core objectives. First, it was aimed to ascertain the relative contributions of several existing accounts of probability matching in determining choice behaviour, particularly regarding the maximization versus diversification of choices. These accounts include failed pattern matching, driven by apophenia, and a heuristic-driven response that can be overruled with sufficient deliberation. Second, to then further address potential mechanisms underlying whichever factor was found to make the most substantive contribution to choice behaviour, through the combined application of behavioural and electrophysiological methods. Over a series of behavioural studies, the use of strategy over intuition proved to be the most consistent and substantial predictor of maximizing choices, in robust support of the heuristic account. Given this finding, the question emerges of why probability matching is the dominant intuitive response. One possibility is that matching represents the overextension of an evolutionarily stable foraging strategy, an account termed the ‘Faulty Foraging Theory’. A simple simulated foraging task was designed to assess choice behaviour when reward schedules incorporate the factor of natural resource accumulation and depletion. The contrast in choice behaviour on this task with the standard probability matching preparation was consistent with the Faulty Foraging model. A series of electrophysiological studies were then conducted, in an attempt to uncover the putative illusory internal representation of reward accumulation on the standard task, which could drive suboptimal diversification of choices. This was ultimately unsuccessful. However, further corroborating electrophysiological evidence was obtained for the heuristic account, in the form of characteristic patterns of prefrontal activity relating to maximizing vs. diversification of choices.